2011
DOI: 10.15684/formath.10.1
|View full text |Cite
|
Sign up to set email alerts
|

REDD Development in Cambodia— Potential Carbon Emission Reductions in a REDD Project

Abstract: Abstract:Foreseeing the importance of managing forests for climate change mitigation and sustainable development, the Royal Government of Cambodia has put strong commitment to managing its remaining forests under the new anticipated international climate change agreement on REDD+ mechanism. Forestry Administration in collaboration with Community Forestry International, and Terra Global Capital started a REDD project for Community Forestry sites in the northern province of Oddar Meanchey in 2007. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
(5 reference statements)
0
19
0
Order By: Relevance
“…There are various methods to predict forest cover change once project is implemented. For simplicity, we followed methods developed by Ty et al [9] to predict the change of forest covers in the PMP,…”
Section: Project Deforestationmentioning
confidence: 99%
See 4 more Smart Citations
“…There are various methods to predict forest cover change once project is implemented. For simplicity, we followed methods developed by Ty et al [9] to predict the change of forest covers in the PMP,…”
Section: Project Deforestationmentioning
confidence: 99%
“…Accordingly, we would conclude that the drivers of deforestation and forest degradation in PMP were conversion of agriculture land, conversion to settlement, annual fire, illegal logging, fuelwood collection, extraction of wood for household consumption and use as farm material. Similarly, Ty et al [9] identified drivers of deforestation and forest degradation in a northern province of Cambodia as conversion to cropland, conversion to settlements and migrant encroachment, forest fire due to land clearing, hunter inducing forest fire, illegal logging for commercial sale and timber harvesting for local use. Therefore, the project activities proposed by Ty et al [9] could also be introduced to PMP.…”
Section: Project Deforestationmentioning
confidence: 99%
See 3 more Smart Citations